Contents and Foreword of the ATIKAN Journal, Issue of December 2015 - ATIKAN Journal, Editor (ASPENSI, 2015)
ATIKAN journal will provide a peer-reviewed forum for the publication of thought-leadership articles, briefings, discussion, applied research, case and comparative studies, expert comment and analysis on the key issues surrounding the educational studies in general and its various aspects. Analysis will be practical and rigorous in nature. The ATIKAN journal, with ISSN ISSN 2088-1290, was firstly published on June 1, 2011, in the context to commemorate the Birth of Pancasila (Five Basic Principles of the Republic of Indonesia)â s name in Indonesia. Since issue of June 2011 to date, the ATIKAN journal has been organized and published by Minda Masagi Press, as a publisher owned by ASPENSI (the Association of Indonesian Scholars of History Education) in Bandung, West Java, Indonesia. The ATIKAN journal is published twice a year, i.e. every June and December.Â Bandung, Indonesia: December 30, 2015.Prof. Dr. Haji Endang KomaraSecretary of ASPENSIs Expert Board in Bandung, West Java, Indonesia.Â